The Difference in Concentration Ability Tomato Leaf Extract (Sollanum lycpersicum l.) Against Larvae of Power Kill Aedes aegypti - Nidaul Husna; Erlani; Ashari Rasjid (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The Aedes aegypti mosquito is a vector carrying Dengue Hemorrhagic Fever (DHF) which is commonly found in tropical and subtropical areas which can cause outbreaks and can cause death in a short period of time. Infectious diseases are still a public health problem caused by the mosquito vector Aedes Aegypti, therefore control is needed to break the chain of disease transmission by eradicating using larvicides. The purpose of this study was to determine the effect of different concentrations of tomato leaf extract (Solanum Lycopersicum L.) on the killing power of larvae Aedes Aegypti. This type of research is experimental research. The sample in this study was 20 larvae for Aedes Aegypti each treatment, so a total of 300 larvae used were exposed to tomato leaf extract concentrations of 0.8%, 1%, and 1.2%. Observations were made for 24 hours with an interval of 4 hours and were replicated three times. The results showed that tomato leaf extract (Solanum Lycopersicum L.) on the killing power of larvae Aedes Aegypti at a concentration of 0.8% was able to kill 9 larvae within 24 hours, a concentration of 1% was able to kill 11 larvae within 24 hours, and a concentration of 1 ,2% was able to kill 14 larvae within 24 hours. The conclusion of this study the concentration of 1,2% tomate leaf extract was 70% effective in killing larvae Aedes Aegypti. Keywords : Tomato Leaf Extract, Aedes aegypti Larvae